The Meaning of Sexual Harassment in the Eye of the Beholder: 25 Years After the Enactment of Israel’s Prevention of Sexual Harassment Law - Sima Zach; Rona Cohen; Michal Arnon (Societies, 2025)
This study examines perceptions of sexual harassment in sports 25 years after the enactment of Israel’s prevention of sexual harassment law, building upon a 1999 study by Feigin and Negbi. Utilizing feminist and power relations theories, this research investigates how perceptions have evolved across genders, competitive levels, and coaching statuses. A total of 361 participants, including non-competitive, competitive, and Olympic athletes, completed a questionnaire assessing perceptions of potentially harassing behaviors. The results reveal significant shifts in awareness, particularly among female athletes, across all four factors of sexual harassment examined. The most substantial change was observed in the “Between concern and interest” factor, indicating increased sensitivity to ambiguous behaviors. Olympic athletes and coaches demonstrated heightened awareness compared to non-competitive athletes. Gender disparities persisted, with female participants consistently showing higher sensitivity to potentially harassing behaviors. These findings underscore the need for tailored educational programs, policy revisions, and increased representation of diverse perspectives in sports leadership.